2017
DOI: 10.1159/000481663
|View full text |Cite
|
Sign up to set email alerts
|

Interocular Symmetry of Choroidal Thickness and Volume in Healthy Eyes on Optical Coherence Tomography

Abstract: Background: We aimed to determine the physiological symmetry, with spectral-domain optical coherence tomography, of choroidal measurements in a healthy population in all the areas defined in the Early Treatment Diabetic Retinopathy Study (ETDRS). Methods: One hundred and fifty-four eyes of 77 healthy young adults between the ages of 19 and 32 years were enrolled. Differences in choroidal thickness (CT) and volume (CV) between the left and right eyes were calculated. Normal ranges of absolute interocular differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 24 publications
6
13
0
Order By: Relevance
“…Our findings show similar results as previously described in CT; CT was thickest in the subfoveal areas, becoming thinner towards the nasal or temporal areas [11,17,18,23,24].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings show similar results as previously described in CT; CT was thickest in the subfoveal areas, becoming thinner towards the nasal or temporal areas [11,17,18,23,24].…”
Section: Discussionsupporting
confidence: 92%
“…There are numerous physiological variables such as AL, refractive error, IOP, diurnal variation, other systemic vascular diseases and various drugs that could affect the CT in addition to the different age ranges of the population groups of each study. In this study, we included patients of similar age to avoid the diminution of the CT with age shown in previous works, and AL was a fundamental factor to be taken into account in the measurement of CT [17][18][19][20][21][22]. We tried to exclude confounding factors by looking for young people with good control, and considerable refractive errors were discarded to avoid bias.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the various differences in CTs reported in each paper, most studies 13,[29][30][31][32] indicated that interocular CTs measured in the foveal and parafoveal areas showed overall high correlation coefficients or ICC values (r > 0.8, ICC >0.9). In our study, CTs showed relatively high agreement (r > 0.8, ICC >0.9) at the subfoveal, nasal 5, nasal 6, temporal 1, and temporal 2 points, corresponding to the center and inner ring (3-mm diameter centered on the fovea) of the Early Treatment Diabetic Retinopathy Study (ETDRS) map.…”
Section: Discussionmentioning
confidence: 92%
“…Conversely, a few reports found the CT of the macula was thicker in left eyes than in right eyes. 13,31 The discrepancies among these studies are presumably related to various factors that can influence CT, such as inaccurate measurement, patient demographics (e.g. sex, age, AL, and SE), diurnal variation, and IOP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation